Effectiveness and safety of guselkumab for the treatment of psoriasis in real‐world settings at 24 weeks: A retrospective, observational, multicentre study by the Spanish Psoriasis Group. Issue 2 (17th January 2022) - del Alcázar, Elena; López‐Ferrer, Anna; Martínez‐Doménech, Álvaro; Ruiz‐Villaverde, Ricardo; Llamas‐Velasco, Mª. del Mar; Rocamora, Vicenç; Julià, Marc; Notario, Jaime; Fernández‐Freire, Lourdes Rodríguez; Sahuquillo‐Torralba, Antonio; Vidal, David; Rivera, Raquel; et al.
Abstract: Data on the effectiveness and safety of a drug in real‐world clinical practice complement the evidence from clinical trials, which are carried out in a different setting. Little has been published on the effectiveness and safety of guselkumab in the treatment of psoriasis in clinical practice. The ojective of this study was to assess the effectiveness and safety of guselkumab at 24 weeks in patients with moderate to severe plaque psoriasis in routine clinical practice. A retrospective, multicentre study of adult patients with moderate to severe plaque psoriasis treated with guselkumab for at least 24 weeks was carried out in Spain. We studied 343 patients, 249 of whom were followed for 24 weeks. By week 24, the mean (SD) psoriasis area severity index (PASI) had decreased from 11.1 (7.3) to 1.7 (2.8) (−9.3; [−10.2;‐8.4]), 85.9% of the patients had achieved PASI score of 4 or less and 77.9% a PASI score of 2 or less. In terms of relative PASI response, 59.4% of the patients achieved a PASI‐90 response and 49.0% a PASI‐100 response. On multivariate analysis, two factors reduced the probability of a PASI of 2 or less at 24 weeks: a BMI ≥30 (OR, 0.44; 95% CI, 0.22–0.88) and a greater previous exposure to biologic therapy (OR, 0.69; 95% CI, [0.56–0.84]). Adverse events were rare (9.9%) and led to withdrawal from treatment in only nine patients (2.6%) by the end of the follow‐up period. The results of this study confirm the high efficacy and safety of guselkumab indicated by the clinical trial data. In clinical practice, the absolute PASI score appears to be a better marker of response to treatment than the relative value.